2005
DOI: 10.1002/ijc.21439
|View full text |Cite
|
Sign up to set email alerts
|

Carrier frequency of mutation 657del5 in the NBS1 gene in a population of polish pediatric patients with sporadic lymphoid malignancies

Abstract: Nijmegen breakage syndrome (NBS) is a human autosomal recessive disease characterized by genomic instability and enhanced cancer predisposition, in particular to lymphoma and leukemia. Recently, significantly higher frequencies of heterozygous carriers of the Slavic founder NBS1 mutation, 657del5, were found in Russian children with sporadic lymphoid malignancies, and in Polish adults with non-Hodgkin lymphoma (NHL). In addition, the substitution 643C>T (R215W) has also been found in excess among children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
34
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 26 publications
1
34
0
1
Order By: Relevance
“…8 It could be postulated that the R215W mutation in the Polish population does not contribute to the development of ALL. In accordance with our results is the observation of Chrzanowska et al, 5 who Table 1 Germline mutations of the NBS1 gene identified among common ALL patients Letter to the Editor found no carriers of the R215W mutation among 545 Polish pediatric patients with lymphoid malignancies. A further mutation in exon 6, identified in a single individual only, was the amino-acid substitution V210F.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…8 It could be postulated that the R215W mutation in the Polish population does not contribute to the development of ALL. In accordance with our results is the observation of Chrzanowska et al, 5 who Table 1 Germline mutations of the NBS1 gene identified among common ALL patients Letter to the Editor found no carriers of the R215W mutation among 545 Polish pediatric patients with lymphoid malignancies. A further mutation in exon 6, identified in a single individual only, was the amino-acid substitution V210F.…”
supporting
confidence: 93%
“…The association of the 657del5 mutation with increased risk of hematological cancer has been recently shown. 3,5 In our study, we observed only one 657del5 mutation in c-ALL patients (1/134) and one in controls (1/195). Similar results were reported by several authors who failed to detect a significant contribution of the 657del5 mutation to lymphoproliferative disease development among both Slavic populations 5 and non-Slavic populations, such as in Germany 5 or Britain.…”
mentioning
confidence: 41%
See 1 more Smart Citation
“…(28,29) The aim of our research was to assess whether mutations in the NBS1 gene may contribute to the development of larynx cancer (LC) and MPT of the head and neck.…”
mentioning
confidence: 99%
“…(21) Recent studies strongly suggest that heterozygous 657del5 mutation carriers have an elevated risk of malignant tumor development, especially of melanoma, (22,23) colon and rectum cancer, (23) prostate cancer, (24) ovarian cancer, (25) breast cancer (26,27) and NHL. (28,29) The aim of our research was to assess whether mutations in the NBS1 gene may contribute to the development of larynx cancer (LC) and MPT of the head and neck.…”
mentioning
confidence: 99%